PERANCANGAN FRONT END PADA WEBSITE SEKOLAH: PERANCANGAN FRONT END PADA WEBSITE SEKOLAH - Sofyan Mufti Prasetiyo; Muhamad Andri; Sarah Fauziah; Syarifatul Maftuha; YULIAN ADI PRASTYO (CV. Multi Kreasi Media, 2022)
Front end is everything that connects the user with the back end system. Usually it is a user interface where the user will interact with the system. Arhandi (2016). One Roof Public Middle School 01 Ciseeng is a junior high school in Ciseeng District, Bogor Regency. Every year, new students will be admitted. In these activities, they often face problems because the system used is still manual, by coming directly to school. With this system, it is hoped that it can help convey information and make it easier to process and manage new student admissions data. The methods used in this research are interviews, literature study, system design, and implementation. From this research, it is hoped that the information system created can provide convenience in implementing new student admissions at One Roof Middle School 01 Ciseeng according to the established flow, and can solve existing problems.